The Improvement of Financial Reporting Skill in Small Medium Enterprises - Hera Khairunnisa; Hafifah Nasution; Etty Gurendrawati (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
ABSTRACTCommunity Service (PKM) is intended to improve financial reporting capabilities by Segara Jaya Village business people. In the process of analyzing the situation, the PKM team found a problem in the Segara Jaya Village business actors, namely that they had not yet separated the notes on their business activities with their personal needs. This has an impact on the difficulty of business actors to know the profits from their business activities. From the analysis of the situation, the servant carries out the service. The method used is a workshop with a simple recording simulation of their business activities.Keywords: community service; financial report; business activities.